2011
DOI: 10.1017/s0007114511004077
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of advanced glycation end-product formation on eye lens protein by rutin

Abstract: Formation of advanced glycation end products (AGE) plays a key role in the several pathophysiologies associated with ageing and diabetes, such as arthritis, atherosclerosis, chronic renal insufficiency, Alzheimer's disease, nephropathy, neuropathy and cataract. This raises the possibility of inhibition of AGE formation as one of the approaches to prevent or arrest the progression of diabetic complications. Previously, we have reported that some common dietary sources such as fruits, vegetables, herbs and spice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…From these data, we can say that rutin is likely the main PC responsible of the antiglycation power of CsME and AChE inhibition ability. In fact, a multitude studies suggested that rutin presented antiglycation power (Cervantes-Laurean et al, 2006;Muthenna, Akileshwari, Saraswat, & Bhanuprakash Reddy, 2012;Nagasawa et al, 2003), inhibited α-glucosidase (Li, Zhou, Gao, Bian, & Shan, 2009), and exhibited antidiabetic action (Suan Chua, 2013). Moreover, a study (Richetti et al, 2011) reported the neuroprotective effect of rutin against scopolamine-induced memory impairment in zebrafish.…”
Section: Glycation Reaction Induces Modifications Of Protein Second-mentioning
confidence: 99%
“…From these data, we can say that rutin is likely the main PC responsible of the antiglycation power of CsME and AChE inhibition ability. In fact, a multitude studies suggested that rutin presented antiglycation power (Cervantes-Laurean et al, 2006;Muthenna, Akileshwari, Saraswat, & Bhanuprakash Reddy, 2012;Nagasawa et al, 2003), inhibited α-glucosidase (Li, Zhou, Gao, Bian, & Shan, 2009), and exhibited antidiabetic action (Suan Chua, 2013). Moreover, a study (Richetti et al, 2011) reported the neuroprotective effect of rutin against scopolamine-induced memory impairment in zebrafish.…”
Section: Glycation Reaction Induces Modifications Of Protein Second-mentioning
confidence: 99%
“…On the contrary, rutin derivatives markedly inhibit AGEs formation (Muthenna, Akileshwari, Saraswat, & Reddy, 2012), modify the extracellular matrix structure, and prevent the abnormal protein accumulation (Kamalakkannan & Prince, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of secondary cataract like diabetic cataract, the protein breakdown process is accelerated during hyperglycemia. Aldose reductase facilitates the transfer of glucose into sorbitol, which is impermeable to the membrane; accumulation of sorbitol ends with glycative and osmotic stress [ 89 ]. Any injury pertaining in the lens tissue may lead to hydration of the protein causing dense cortical cataract.…”
Section: Cataract: a Progressive Deterioration Of Visionmentioning
confidence: 99%
“…Aldose reductase facilitates the conversion of glucose to sorbitol using NADPH as the cofactor. Accumulation of sorbitol results in osmotic swelling, osmotic gradient, and tissue damage [ 89 ]. The patho-mechanism is convicted by the formation of advanced glycation end products, the end products of millard reaction culminates in lens protein alteration.…”
Section: Glycation a Rudimentary Factor Of Diabetic Cataractmentioning
confidence: 99%